Assessment of the relationship between morphological emphysema phenotype and corresponding pulmonary perfusion pattern on a segmental level - Bryant, Mark; Eberhardt, Ralf; Menezes, Ravi; Herth, Felix; Sedlaczek, Oliver; Kauczor, Hans-Ulrich; Ley-Zaporozhan, Julia (European radiology, 2015)
Distinct morphological emphysema phenotypes were assessed by CT to show characteristic perfusion defect patterns.
Gesehen am 14.10.2020
Published: 28 August 2014